DEVELOPING ESP NURSING BASED ON COMMUNICATIVE LANGUAGE TEACHING - Febrijanto, Yoyok; Kurniajati, Sandy (English Education:Journal of English Teaching and Research, 2017)
ESP nursing materials is an important component in the success of educational programs, especially in the field of nursing. The development of English learning is now more emphasis on the authenticity of the material that is contextual activities or work involved, one of which is in nursing profession. Communicative language teaching (CLT) sets principles about the teaching of communicative competence not confined to verbal communication but also includes written communication, consists of four skills especially on ESP nursing based on nursing care (assessment, nursing diagnosis, planning(intervention & implementation, and evaluation) as the main source of objective achievement in teaching learning process. The development method used is adapted from Borg and Gall's model involved 24 students, 1 expert in English education, 2 experts in nursing education, and 1 practitioner of hospital. Researchers developed materials (4 chapters) based needs analysis (students’ need and reviewing existing syllabus) with four language skills. Result of expert validation (materials evaluation based on contents, exercises, communication, and general elements) was very good (average score 3.5) and result of students’ try out to give the decision of the product quality, the average score was 3.2, it meant the materials was acceptable and eligible to be used by the nursing students as autonomous learning. In conclusion, the final product can be used as a model of instructional materials to teach English nursing as ESP materials. Keywords: ESP Nursing, CLT, Material Development